EFFECT OF ZEOLITES SPEREADING ON LITTERS TO BROILER PERFORMANCES REARED UNDER DIFFERENT FLOOR SPACES - Dede Kardaya; Niken Ulupi (Institut Teknologi Bandung, 2006)
Effect of zeolites spreading on litters to broiler performances under different floor spaces had been performed in five weeks. As many as 324 chicks of a day-old Hubbard strain were fed rations contained 3,000